Do teenagers return to normal physical activity levels after limb fractures? A longitudinal, accelerometry-based, activity monitoring study. (December 2019) - Maggio, A. B. R.; Martin, X.; Steiger, C.; Tabard-Fougère, A.; Dayer, R.; Delhumeau, C.; Ceroni, D.
Abstract: Purpose: This study aimed to elucidate whether levels of physical activity (PA) return to normal after bone healing or whether long-term behavioural changes in PA are to be expected in children and teenagers who have sustained limb fractures. Methods: In all, 100 children and teenagers with a first episode of limb fracture and 100 sex- and age-matched healthy controls (CTRL) were recruited for a prospective study. PA in limb fracture patients was assessed at 18-month follow-up using accelerometer measurements, and values were compared with those of CTRL. Time spent in PA at different levels of intensity was determined for each participant and expressed in minutes and as a percentage of total validly measured time. Results: Mean levels of PA at different levels of intensity by previously injured children and teenagers were similar than CTRL (42 sets of paired data). However, time spent in moderate-to-vigorous PA (MVPA) was lower than 60 minutes among limb-fracture patients at 18-month follow-up. Conclusion: The amount of skeletal loading in children and teenagers returns to normal values by 18 months after limb fracture. Even if time spent in MVPA is not significantly lower in children and teenagers with limb fractures, it no longer reached the international recommendations for school-aged children (MVPA > 60 minutes), which may be interpreted as a lifestyle modification or a behavioural change to avoid new trauma. Level of Evidence: II